The diasporic slide: representations of second-generation diasporas in Yasmine Gooneratne's A Change of Skies (1991) and in Chandani Lokugé's If the Moon Smiled (2000) and Softly as I Leave You (2011). Issue 5 (2nd September 2016) - Watkins, Alexandra
Abstract: The novels by Yasmine Gooneratne, A Change of Skies (1991), and Chandani Lokugé, If the Moon Smiled (2000) and Softly as I Leave You (2011), show the challenge of diaspora as sliding from parents to children. These fictions portray second-generation immigrants as "caught between two cultures": the Sri Lankan culture of their parents and the Australian culture with which they engage at school and university. In Gooneratne's comedy this cultural negotiation creates comic ambivalence in the second-generation character Veena, who is set to repeat the actions of her forebears. Gooneratne's playful outcome contrasts with Lokugé's tragic vision in her novels If the Moon Smiled and Softly as I Leave You, which position the "model minority" stereotype and racism in Australia, respectively, as significant challenges for second-generation characters. This article aims to counterbalance the dominant critical focus on first-generation diaspora in fiction. It examines relationships between parent and child characters in the novels in the context of social studies on second-generation diaspora, the South Asian diaspora, and multiculturalism in Australia.